Exploring the role of intestinal microbiota in mitigating acute radiation-induced intestinal injury through high-energy X-ray FLASH radiotherapy via metagenomic analysis - Du, Huan; Hao, Xiaofei; Lin, Binwei; Zhu, Yihan; Yang, Yiwei; Tang, Mingming; Wu, Wei; Wang, Decai; Lin, Bo; Liang, Yuwen; Tang, Wenqiang; Xu, Haonan; et al. (Frontiers in Microbiology, 2025)
ObjectivesThis study preliminarily examines the potential correlation between the gut microbiome and the protective effects of FLASH radiotherapy (FLASH-RT) on intestinal tissue using metagenomic analysis.MethodsCompact single high-energy X-ray source (CHEXs) FLASH-RT was employed for FLASH irradiation, while EBT3 radiochromic film and a fast current transformer were used to measure the absolute dose and the pulsed beam characteristics. Sham radiotherapy (control), FLASH-RT (333 Gy/s), and Conventional dose rate radiotherapy (CONV-RT, 0.07 Gy/s) were performed on whole abdomen of normal C57BL/6J female mice (10 Gy, 12 Gy, 14 Gy). At 72 h post-irradiation, intestinal contents from normal C57BL/6J female mice were collected for metagenomic analysis. The survival status, body weight, and damage to normal tissues were observed.ResultsAt 28 days post-whole abdomen irradiation with doses of 12 Gy, the survival rate of the FLASH group was higher than that of the CONV group (p < 0.05). Histological analysis of intestinal tissues by H&E staining revealed significantly less acute intestinal damage and inflammation in the FLASH group compared to the CONV group. Further macrobiome analysis using LEfSe indicated that the abundance of beneficial bacteria, including Weissella, Lactobacillus ruminis and Lactobacillus taiwanensis was significantly higher in the FLASH group than in the CONV group. Moreover, compared to the CONV group, the FLASH group exhibited significant upregulation of several signaling pathways, including the glycosaminoglycan degradation, PI3K/Akt and arabinogalactan biosynthesis Mycobacterium signaling pathway.ConclusionCompared to CONV-RT, high-energy X-ray FLASH irradiation exerts radioprotective effects on normal intestinal tissue. Alterations in the gut microbiota and associated signaling pathways may be linked to the protective effects of FLASH.